Measuring growth potential: a geo-archaeological study of settlement location selection and associated land management practices in Bokoni, Mpumalanga - Solomon, Lauren Leontine (My University, 2016)
The economy of Bokoni was centred on farming, with terrace agriculture playing a fundamental role in the construction and location of village sites. This dissertation examined the recursive relationship between soil chemistry and site location at three Bokoni sites: Doornkop, Khutwaneng and Kranskloof. These sites represent the three different phases of occupation in Bokoni. Analysis focused on the correlation of Ca, Mg, K, P, NH4, NO3, CEC and %C to the site contexts. At a macro scale there are substantial similarities with regards to the geology and the soil chemistry; suggesting a strong preference for locating village sites on relatively nutrient rich clay soils. On a more localised scale chemical analysis of the different contexts of these sites (i.e. domestic areas, central enclosures, terraces and non-archaeological areas) explored the agricultural potential of the soil in the various areas. These analyses showed a distinct difference in agricultural potential of soils in stone walled areas. This profile was the result of the nutrient contribution from the underlying soils in combination with either enrichment at the time of occupation, or the ongoing influence of the stone walled structures on the soils. The enrichment of soil in residential sites, whether intentional or accidental, could explain why Bokoni villagers continually reused sites during the earlier part of the sequence, before violence repeatedly disrupted settlement, and thus choice of settlement location, in the area.
A Dissertation submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science. Johannesburg, 2016.
Keywords: Agricultural systems; Agriculture--South Africa--Mpumalanga; Agriculture--Economic aspects--South Africa--Mpumalanga; Traditional farming--South Africa--Mpumalanga; Land use--Management